Education and Mental Health Through Artificial Intelligence Virtual Assistant - Ioniță, David-Theodor; Bogdan, Ioana Corina; Modran, Horia Alexandru; Dinu, Alexandru (Springer Nature Switzerland, 2025)
With the evolution of technology in daily life, there is a growing opportunity to leverage Artificial Intelligence (AI) to support students. Existing solutions demonstrate that AI can personalize learning and assist with health management, but there is still a gap in integrated, companion-based AI systems that can seamlessly operate in both domains. This paper introduces EduPal, an innovative virtual assistant designed to enhance educational experiences and provide psychological support. Leveraging advancements in AI, EduPal offers personalized learning experiences and mental health assistance, tailoring its interactions based on user-specific profiles and psychological assessments. The system employs the GPT-4 language model, facilitating natural language interactions through voice and text, and integrates advanced algorithms for real-time response generation. EduPal aims to assist in academic subjects, generate tailored exercises, and provide timely psychological interventions, thereby improving educational outcomes and emotional well-being. Future work will focus on enhancing system capabilities, ensuring data privacy, and broadening the scope of its applications. The potential of EduPal to transform personal education and health management underscores the significant impact of AI-driven virtual assistants in modern society.